Effects of an extrinsic constraint on the tennis serve - Mendes, P. C.; Santos Couceiro, M.; Rocha, R.; Manuel Clemente, F.; Lourenco Martins, F. M.; Mendes, R. M.; Fuentes Garcia, J. P. (International Journal of Sports Science and Coaching, 2015)
This study analysed the extrinsic constraint of induced aerodynamic flow (IAF) on the first serve by expert tennis players with temporal organization of the movement, as well as the velocity and amplitude of the racket motion analyzed. Twelve expert right-handed tennis players voluntarily participated in this study. Each player performed 20 trials without IAF and another 20 trials for each different speed configuration of induced crosswind: 2.4 m/s; 4.3 m/s; 5.8 m/s; and random speed. The coefficient of variation, r-pearson test and the inferential test one-way ANOVA were used to compare movement data. The results suggest spatio-temporal adjustments depending on the wind speed. Moreover, statistical differences were identified on both the temporal organization of the serve and on the racket`s motion amplitude and velocity. The intra- and inter-individual variability of the motor behavior shows the uniqueness of the serve movement of each player.